Implementasi Asesmen Autentik Al-Qur’an Hadits: Studi Kasus Al-Islam Giwangan Yogyakarta - Matofiani, Reni; Prastowo, Andi (Journal of Islamic Education, 2022)
Education is very important in human life. Therefore, with education, it is necessary to have an assessment that can measure whether the learning that has taken place is in accordance with the objectives or core competencies. So authentic assessment plays a very important role in measuring the domains of attitudes, skills and knowledge. The purpose of this study is to describe the implementation of authentic research in learning the Qur'an Hadith at MI Al-Islam Giwangan Yogyakarta. Meanwhile, this research method uses case study research with a qualitative approach. The result of this study is that the implementation of an authentic assessment of class XI on the subjects of the Qur'an hadith at MI Al-Islam Giwangan Yogyakarta has been carried out well, covering the assessment of the cognitive, affective, and psychomotor domains. In the cognitive domain, the teacher uses assignment techniques, quizzes, midterm exams, and final exams. Specifically for the affective domain, the teacher uses observation, self-assessment, and peer-assessment techniques. The psychomotor domain uses the technique of expressing opinions, discussions, and rearranging the truncated verses, both hadith and projects. While the evaluation that needs to be improved is the lack of enthusiasm for learning for students and inadequate classrooms for students.